Professional training of legal specialists at a university: new requirements and modern approaches - Yuri Nalbievich Nagarokov (Вестник Майкопского государственного технологического университета, 2023)
The article substantiates the relevance of improving the quality of professional training of future lawyers at a university due to the new requirements for the competence of legal experts in the context of improving Russian statehood and society. The following approaches to the professional training of lawyers have been revealed on the basis of analysis, generalization and systematization of studies of the problem of legal development: deontological approach, aimed at the formation of a value attitude to the profession and professional identity; development of soft skills as key competencies, mastery of which contributes to career growth; dual training and mentoring, providing professional socialization of future specialists. The requirements for a modern lawyer have been formulated: lifelong learning, image building, public speaking, knowledge of information and communication technologies. The possibilities of dual training for the organization of mentoring have been considered, such as training practical skills by a highly qualified specialist, which ensures not only the transfer of professional skills, but also the formation of a value attitude to the profession, professional socialization skills and soft skills. A legal clinic providing a combination of dual training with mentoring, meeting current trends in the development of FSE and professional training of legal specialists is considered as a form of practice. Such methods as analysis, synthesis, analogy and modeling have been used in the research. The conclusion is drawn about the advantages of using the considered approaches and forms of training that increase the practical orientation of educational programs. The materials of the article can be used as the basis for the development of funds for assessment tools and put into the practice of higher educational institutions.